Out of sight out of rights: Rejected asylum seekers and closed-files individuals in Egypt - Abdel Aziz, Nourhan Amr (AUC Knowledge Fountain, 2018)
According to international law, everyone has the right to seek asylum; however, not every asylum seeker receives refugee status. Individuals whose asylum claims are rejected often stay in their country of destination out of fear of returning back to their countries of origin. Such populations are known as rejected asylum seekers and closed-files and in Egypt they are often found among the Sudanese, South Sudanese, Ethiopian, Eritrean, and Somali communities. This thesis focuses on the rights and entitlements of rejected asylum seekers and closed-files individuals who remain in Egypt after having their asylum claim rejected by UNHCR. The thesis argues that rejected asylum seekers have rights under international law but are not accessing and enjoying them in Egypt. To make this argument, the thesis answers two central questions: 1) What are the rights of rejected asylum seekers according to international and national laws; and 2) Are rejected asylum seekers receiving and enjoying these rights in Egypt? The thesis begins with an analysis of the international legal framework governing the rights of different categories of migrants. An analysis of the gaps in the international legal framework is also provided. An analytical overview on the legal, policy, and institutional frameworks governing migrants and refugees in Egypt and consular policies is presented. The situation of rejected asylum seekers is analyzed and the protection gaps identified.